When in Rome: How Non-domestic Companies Listed in the UK May Not Comply with Accepted Norms and Principles of Good Corporate Governance. Does Home Market Culture Explain These Corporate Behaviours and Attitudes to Compliance? - Rejchrt, Peter; Higgs, Malcolm (Journal of business ethics, 2015)
Non-domestic companies are increasingly present on the London Stock Exchange. Such companies have specific governance requirements. They may seek to access capital in a more liquid market and to diversify ownership. The reputational 'bonding' (Coffee, Northwest Univ Law Rev 93:641–708, 1999; Columbia Law Rev 101:1757–1831, 2002) to a prestigious exchange should be a statement to the market of a propensity to disclosure and a willingness to protect minority shareholders. Yet, many non-domestic companies retain tightly controlled shareholding structures and are based in emerging regions where national culture norms differ to the UK. We hypothesise that non-domestic companies are likely to be less compliant with the principles of the UK Corporate Governance Code and suggest a correlation between lower levels of compliance and non-domestic companies from countries that demonstrate high power distance in the Hofstede (Culture's consequences: International differences in work-related values, 1980a) cultural value framework. We find some encouraging signs of compliance with the reigning governance code principles in Board structures. However, we find only partial compliance in leadership and Board effectiveness measures in those companies from cultures high on the power-distance scale. Further, we include analysis into ownership characteristics and find companies from emerging markets are dominated by a single or controlling group of shareholders, which is likely to impact on attitudes to compliance and is particularly evidenced in terms of Board structures with no executive directors or led by an executive Chairman. Much of the prior research effort into the levels of compliance with the UK's 'comply-or-explain' approach to governance has produced mixed results and focused on all companies. In our exploratory approach to analysing only the non-domestic subsample, we report some evidence linking cultural distance to lower levels of compliance with the UK standards. We develop a framework to guide future research into the context and cultural underpinnings of this sub-sample of companies, hypothesising that frequent market capitalisation-induced index changes may divert attention away from any potential compliance issues. On the one hand, our evidence is encouraging for governance regimes based on voluntary compliance disclosures such as the UK and similar European and international markets, as we report partial compliance with the principles of the current governance code. Our research may, however, be helpful in guiding future versions of the UK governance framework and other international governance regimes adopting the 'comply-or-explain' approach and in setting policy to improve disclosure. It contributes to the understanding of the specific context of non-domestic companies and any cultural tendencies to non-compliance. By demonstrating evidence of lower levels of compliance with key principles of the Code by non-domestic companies, we present a framework enabling lawmakers to further improve corporate governance codes.